KUALITAS PELAYANAN JAMINAN PERSALINAN (JAMPERSAL) DI RSUD PORSEA KABUPATEN TOBA SAMOSIR - Nababan, Desi F Sari; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The factor of Infrant Mortality Rate (IMR) and Maternal Mortality Rate (MMR) in Indonesia made goverment to make The Giving Birth Guarantee program (Jampersal) for the pregnant lady. The purpose of this research is to know The quality service of The Giving Birth Guarantee program (Jampersal)successful service in RSUD PorseaKabupaten Toba Samosir and the factors that influence the quality service ofThe Giving Birth Guarantee program (Jampersal)) in RSUD Porsea Kabupaten Toba Samosir.The theory concept that used is by Parasuraman et al, which is consist of five indicators; Reability, Responsiveness, Assurance, Emphaty, and Tangibles. This research used qualitative research method. The needed data was collecting throughinterview,observationand documentation. The informants of this research were Director of RSUD Porsea, The Chief of Service sector in RSUD Porsea, Medic team, nurses and staffs in RSUD Porsea, patients in RSUD Porsea. The technic of data analysis used was descriptive qualitative.The result of this research showed that the service of the Giving Birth Guarantee program (Jampersal) in RSUD Porsea Kabupaten Toba Samosir was good because patient who used the Giving Birth Guarantee program (Jampersal) in RSUD Porsea feel that four of five indicators have already done well, which are Reability, responsiveness, assurance, emphaty, meanwhile for Tangibles needed to fix, and there were factors which influence the quality of service of the Giving Birth Guarantee program (Jampersal), they were Human Resources, Leadership and budget.Key word: Health Service, Program, Jaminan Persalinan (Jampersal)